Calculation of the rating of ecological development of individual regions of the Republic of Belarus in 2021 - Hramadskaya, Alena; Tsublianok, Darya; Vadeika, Marharyta (Journal of the Belarusian State University. Ecology, 2023)
The article is aimed at informing the public and all interested parties about the work carried out to calculate the rating of environmental development of individual regions of the country, the results obtained and the score ratio of the administrative territories under consideration relative to each other. The rating of ecological development of the regions of the Republic of Belarus is intended to reflect the activities in the field of rational nature management and environmental protection of state bodies whose competence includes environmental protection issues, executive authorities, public associations, citizens in the relevant territories with the possibility of comparing information in the administrative-territorial context. It serves as an information basis for making environmentally significant decisions to improve environmental policy, environmental management and environmental protection mechanisms, monitoring compliance with environmental legislation, evaluating the effectiveness of environmental protection measures, developing regional programs, as well as scientific and technical developments aimed at ensuring environmental safety and sustainable environmental management. This article contains the results of calculating the rating of environmental development of the regions of the regional centers, Minsk, Brest, Vitebsk, Gomel, Grodno, Minsk and Mogilev districts in 2021. As well as a comparative characteristic of the calculation of the rating of 2021 by 2020 for regional centers and Minsk of the Republic of Belarus. The initial data for calculating the environmental development rating indicators of regional centers, Minsk and districts are the data generated in accordance with the TAP 17.02-19-2021 (33140) “Environmental protection and nature management. Rating of ecological development of the regions of the Republic of Belarus. Technical requirements” by public administration bodies, organizations subordinate to the Government of the Republic of Belarus, local authorities (district executive committees, Brest, Vitebsk, Gomel, Grodno, Minsk, Mogilev city executive committees), territorial bodies of the Ministry of Natural Resources and subordinate organizations, other organizations of the Republic of Belarus. The methodology for calculating the rating of environmental development of cities and districts is also given in the TAP 17.02-19-2021, which describes in detail the sequence, formulas, the formation of complexes of indicators into groups of indicators for detailed and correct calculation. The main results of the article were the ranking of cities and districts according to a set of indicators that touched upon issues of environmental protection and rational use of natural resources, as well as issues of the effectiveness of environmental policy at the regional level. For example, in 2021 Brest and Mogilev region became the leaders, however, Gomel and Minsk region became the lowest number of points in the year under review.
Keywords: еnvironmental rating; environmental impact; environmental protection; comprehensive assessment; environmental condition; environmental indicators